Issledovanie sorevnovatel'noi deyatel'nosti junych sportsmenov-orientirovshchikov - Voronov, Yu. S. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Article studies the competitive activities of young athletes-orienteers. The structure of competitive distances in orienteering for young athletes in the age of 10-16 is shown as well as the technical parameters when taking part in a competition. The structure of competitive distances during World Championships for the age of M-21 is alspo presented.